2023
DOI: 10.1038/s41419-023-05873-2
|View full text |Cite
|
Sign up to set email alerts
|

SMURF1 attenuates endoplasmic reticulum stress by promoting the degradation of KEAP1 to activate NRF2 antioxidant pathway

Abstract: Cancer cells consistently utilize the unfolded protein response (UPR) to encounter the abnormal endoplasmic reticulum (ER) stress induced by the accumulation of misfolded proteins. Extreme activation of the UPR could also provoke maladaptive cell death. Previous reports have shown that NRF2 antioxidant signaling is activated by UPR and serves as noncanonical pathway to defense and reduce excessive ROS levels during ER stress. However, the mechanisms of regulating NRF2 signaling upon ER stress in glioblastoma h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Indeed, previous studies in proteinopathies showed that Nrf2 activation inhibited the formation and/or reduced the number of existing aggregates of α-synuclein [ [97] , [98] , [99] , [100] ], amyloid beta [ [101] , [102] , [103] , [104] ] and tau [ [105] , [106] , [107] ], whereas Nrf2 deficiency promotes protein aggregation [ [108] , [109] , [110] ]. The Nrf2 transcription factor has long been identified as a modulator of autophagy [ [111] , [112] , [113] , [114] ], and is also associated with the Unfolded Protein Response (UPR) [ 100 , [115] , [116] , [117] , [118] , [119] , [120] ], which might explain its ability to reduce pathologic protein aggregation in several proteinopathies, including prion diseases [ 121 , 122 ]. Interestingly, activation of the UPR has been utilized as a potential treatment against CJD [ 123 ], whereas p62 mediated Nrf2 activation and subsequent upregulation of autophagy levels has been proposed as a therapeutic strategy for prion diseases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies in proteinopathies showed that Nrf2 activation inhibited the formation and/or reduced the number of existing aggregates of α-synuclein [ [97] , [98] , [99] , [100] ], amyloid beta [ [101] , [102] , [103] , [104] ] and tau [ [105] , [106] , [107] ], whereas Nrf2 deficiency promotes protein aggregation [ [108] , [109] , [110] ]. The Nrf2 transcription factor has long been identified as a modulator of autophagy [ [111] , [112] , [113] , [114] ], and is also associated with the Unfolded Protein Response (UPR) [ 100 , [115] , [116] , [117] , [118] , [119] , [120] ], which might explain its ability to reduce pathologic protein aggregation in several proteinopathies, including prion diseases [ 121 , 122 ]. Interestingly, activation of the UPR has been utilized as a potential treatment against CJD [ 123 ], whereas p62 mediated Nrf2 activation and subsequent upregulation of autophagy levels has been proposed as a therapeutic strategy for prion diseases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%